Legal Protection of Registered Marks given Law Number 20 of 2016 concerning Brands and Geographical Indications - Habib, Yahya Abdul; Nurwati, Nurwati (IJBLE Scientific Publications Community Inc., 2024)
This research examines the legal protection of registered trademarks based on Law Number 20 of 2016 and handles registered trademark disputes in legal protection initiatives. Even though this research is descriptive and analytical, the author uses normative legal techniques. Article 35 of Law Number 20 of 2016 states that brand protection only applies to registered marks. Ten (10) years are allowed to protect a registered trademark upon receipt, and this period may be extended. The purpose of protecting a registered trademark is to give the owner of the trademark exclusive (special) rights and specific legal remedies that he can take. If there is substantial similarity or malicious intent behind the trademark issue,